Elimination of aromatic fusel alcohols as by-products of Saccharomyces cerevisiae strains engineered for phenylpropanoid production by 2-oxo-acid decarboxylase replacement - Hassing, Else-Jasmijn; Buijs, Joran; Blankerts, Nikki; Luttik, Marijke A.; Hulster, Erik A.de; Pronk, Jack T.; Daran, Jean-Marc (Metabolic engineering communications, 2021)
Engineered strains of the yeast Saccharomyces cerevisiae are intensively studied as production platforms for aromatic compounds such as hydroxycinnamic acids, stilbenoids and flavonoids. Heterologous pathways for production of these compounds use l-phenylalanine and/or l-tyrosine, generated by the yeast shikimate pathway, as aromatic precursors. The Ehrlich pathway converts these precursors to aromatic fusel alcohols and acids, which are undesirable by-products of yeast strains engineered for production of high-value aromatic compounds. Activity of the Ehrlich pathway requires any of four S. cerevisiae 2-oxo-acid decarboxylases (2-OADCs): Aro10 or the pyruvate-decarboxylase isoenzymes Pdc1, Pdc5, and Pdc6. Elimination of pyruvate-decarboxylase activity from S. cerevisiae is not straightforward as it plays a key role in cytosolic acetyl-CoA biosynthesis during growth on glucose. In a search for pyruvate decarboxylases that do not decarboxylate aromatic 2-oxo acids, eleven yeast and bacterial 2-OADC-encoding genes were investigated. Homologs from Kluyveromyces lactis (KlPDC1), Kluyveromyces marxianus (KmPDC1), Yarrowia lipolytica (YlPDC1), Zymomonas mobilis (Zmpdc1) and Gluconacetobacter diazotrophicus (Gdpdc1.2 and Gdpdc1.3) complemented a Pdc− strain of S. cerevisiae for growth on glucose. Enzyme-activity assays in cell extracts showed that these genes encoded active pyruvate decarboxylases with different substrate specificities. In these in vitro assays, ZmPdc1, GdPdc1.2 or GdPdc1.3 had no substrate specificity towards phenylpyruvate. Replacing Aro10 and Pdc1,5,6 by these bacterial decarboxylases completely eliminated aromatic fusel-alcohol production in glucose-grown batch cultures of an engineered coumaric acid-producing S. cerevisiae strain. These results outline a strategy to prevent formation of an important class of by-products in ‘chassis’ yeast strains for production of non-native aromatic compounds. •Identification of pyruvate decarboxylases active with pyruvate but not with aromatic 2-oxo acids.•Zymomonas mobilis pyruvate decarboxylase can replace the native yeast enzymes.•Expression of Z. mobilis pyruvate decarboxylase removes formation of fusel alcohols.•Elimination of fusel alcohol by products improves formation of coumaric acid.•Decarboxylase swapping is a beneficial strategy for production of non-native aromatics.